Unearthing the evidence: post-mortem interrogation of cardiac implantable electronic devices. (14th October 2021) - Block, T; Paratz, E; La Gerche, A; Stub, D; Strathmore, N; Mond, H; Kistler, P; Kalman, J; Burke, M; Voskoboinik, A
Abstract: Background: The diagnostic yield of post-mortem interrogation of cardiac implantable electronic devices (CIEDs) including pacemakers, defibrillators and implantable loop recorders has not been well described. Methods: We reviewed all post-mortem CIED interrogations performed by our statewide Institute of Forensic Medicine between 2005–2020 for investigation of sudden or unexplained death. Results: 260 patients (68.8% male, median age 72.8 years [IQR 62.7–82.2]) underwent post-mortem CIED interrogation (202 pacemakers, 56 defibrillators and 2 loop recorders). CIEDs were implanted for a median of 2.0 [IQR 0.75–5] years, with 19 devices requiring replacement (and 5 end of life). Post-mortem interrogation was successful in 256 (98.5%) cases. Potential CIED malfunction was identified in 21 (8.1%) cases: untreated ventricular arrhythmias (n=13), lead failures (n=3) and battery depletion (n=5). CIED interrogation directly informed cause of death in 130 (50.0%) cases, with fatal ventricular arrhythmias identified in 121 patients (46.5%). In retrospect, 72 (27.7%) patients had abnormalities recorded by their device in the 30 days preceding death: non-sustained ventricular tachycardia (n=26), rapid atrial fibrillation (n=17), longevity concerns (n=22), intrathoracic impedance alarms (n=3), lead issues (n=3) or therapy delivered (n=1). In 6 cases where the patient was found deceased after a prolonged time, CIED interrogation accurately determined time of death. In one case, CIED interrogation was the primary method of patient identification. Conclusion: Post-mortem CIED interrogation frequently contributes important information regarding critical device malfunction, pre-mortem abnormalities, cause and time of death or patient identity. Device interrogation should be considered for select patients with CIEDs undergoing autopsy. Funding Acknowledgement: Type of funding sources: None.